2023
DOI: 10.1175/mwr-d-22-0039.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Rapid Weakening of Typhoon Trami (2018): Strong Sea Surface Temperature Cooling Associated with Slow Translation Speed

Abstract: This work investigates the rapid weakening (RW) processes of Typhoon Trami (2018) by examining sea surface temperature (SST) cooling based on air-sea coupled simulations during typhoon passage. The cold wake and Trami’s RW occurred as the storm was moving at a very slow translation speed. A marked structural change of Trami is found in a three-dimensional ocean-coupled model experiment during the RW stage, in which the convective clouds and convective bursts in the inner core of the simulated TC dramatically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Figure 11 shows the spatial distributions of SST and zonal vertical cross-sections along 20.4° N at 0000 UTC 24 September (before the storm's arrival) and 0000 UTC 27 September (during the storm). The maximum SST cooling reached about 6 °C just behind the storm center, which is in good agreement with the observations and model results from previous studies [31,[33][34][35][36]. The slow propagation…”
Section: Peer Review 10 Of 21supporting
confidence: 92%
See 2 more Smart Citations
“…Figure 11 shows the spatial distributions of SST and zonal vertical cross-sections along 20.4° N at 0000 UTC 24 September (before the storm's arrival) and 0000 UTC 27 September (during the storm). The maximum SST cooling reached about 6 °C just behind the storm center, which is in good agreement with the observations and model results from previous studies [31,[33][34][35][36]. The slow propagation…”
Section: Peer Review 10 Of 21supporting
confidence: 92%
“…Figure 11 shows the spatial distributions of SST and zonal vertical cross-sections along 20.4° N at 0000 UTC 24 September (before the storm's arrival) and 0000 UTC 27 September (during the storm). The maximum SST cooling reached about 6 °C just behind the storm center, which is in good agreement with the observations and model results from previous studies [31,[33][34][35][36] According to the JTWC best track data, Trami reached its peak intensity of 914 hPa at 1800 UTC 24 September and gradually weakened thereafter (Figure 2). This is consistent with our model simulation during Trami's weakening phase.…”
Section: Peer Review 10 Of 21supporting
confidence: 91%
See 1 more Smart Citation
“…The negative feedback of SSC to typhoon intensity requires that typhoon can have a long enough residence time on the cold wake. Therefore, past studies have shown that the translation speed of typhoons [17][18] and other related factors [19] together become important factors affecting the intensity of typhoons. In order to improve typhoon intensity forecasting skills, the numerical simulations are applied to explore the negative feedback mechanism of SSC to typhoon intensity [20] .…”
Section: Introductionmentioning
confidence: 99%